ЕЛ БАСҚАРҒАН АНАЛАРДЫҢ ТАРИЙХТА ҚАЛДЫРҒАН ИЗЛЕРИ - Зарипова, З.С. (FAN va JAMIYAT, 2022)
This article provides epic information about the rulers and female heroes during the Massagets period. The influence of rulers and women heroes in epic works on the appearance of brave girls is described. The development of the theme is based on historical information and scientific decisions of researchers about the ruler of the Scythians, Akkagas. The article mentions the appearance in folk works of images of heroines in the basis of images of rulers.